ANALISIS PENGGUNAAN APLIKASI SI MAS BAIK (SISTEM MANAJEMEN SURAT BERBASIS ELEKTRONIK) DALAM PENGELOLAAN ARSIP SURAT MASUK BERBASIS ELEKTRONIK DI BIRO PEMERINTAHAN DAN OTONOMI DAERAH SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Rofiqoh Azmi, Putri; Arlupi Utami, Dian (Universitas Negeri Surabaya, 2024)
Archives have an important role as a source of information in an organization or agency to expedite administrative activities. With the development of current technology that has affected all organizations, computer technology is a means of information media that is used to manage data quickly and effectively. Especially in making it easier for employees to work on the archive management process. Utilization of computer technology can make manual archives virtual and can create electronic archives. However, there are still cases in several agencies where in fact they are still not ready to keep up with technological developments in the process of managing electronic records, so that the results of administrative activities are still in the form of paper documents which often create problems with storage space, maintenance costs, and other factors that cause damage to files. This study aims to describe the analysis of the use of the SI MAS BAIK application (Electronic-Based Mail Management System) in managing electronic-based incoming mail archives at the Bureau of Government and Regional Autonomy at the Regional Secretariat of East Java Province. The method used in this research is descriptive qualitative research method. The focus of this research is on the electronic archive life cycle which includes: (1) the creation and storage stages; (2) the stage of use and distribution; (3) maintenance stage; (4) disposition stage. The data analysis technique in this study is by collecting data, reducing data, presenting data, and drawing conclusions. The results showed an analysis of the use of the SI MAS BAIK application (Electronic-Based Mail Management System) in managing electronic-based incoming mail archives at the Bureau of Government and Regional Autonomy Regional Secretariat of East Java Province through the stages of the electronic archive life cycle according to Read and Gin in (Muhidin & Winata) in (Aulia & Kurniawan, 2022), namely the creation and storage stage, the use and distribution stage, the maintenance stage, and the disposition stage. The Bureau of Government and Regional Autonomy has only gone through one stage which has been well implemented, namely the use and distribution stage. However, at the creation and storage stage, the maintenance stage, and the disposition stage need attention. Keywords: management, archives, electronics